2019
DOI: 10.3390/batteries5040075
|View full text |Cite
|
Sign up to set email alerts
|

Future Portable Li-Ion Cells’ Recycling Challenges in Poland

Abstract: The paper presents the market of portable lithium-ion batteries in the European Union (EU) with particular emphasis on the stream of used Li-ion cells in Poland by 2030. In addition, the article draws attention to the fact that, despite a decade of efforts in Poland, it has not been possible to create an effective management system for waste batteries and accumulators that would include waste management (collection and selective sorting), waste disposal (a properly selected mechanical method) and component rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…In addition to a host of electrified mobility startups [123], Hyundai will commence an EV manufacturing plant in 2023 [124] and the operation of an onshore LIB recycling plant (TES-AMN group) has already commenced [125]. In contrast, a recent publication highlighting the efforts of Poland to develop onshore capability to recycle LIBs has shown that after 10 years of interest by a variety of stakeholders in the battery supply chain, it has not been able to develop, suggesting that government policies and monetary incentives play a key role [126]. Likewise, Australia's neighbours in the Asia-Pacific region are commencing their transition to renewable energy generation and storage and, therefore, opportunities exist for Australia to develop supply chains in the local region.…”
Section: Influence Of Global and Government Policies-lowering Emissio...mentioning
confidence: 99%
“…In addition to a host of electrified mobility startups [123], Hyundai will commence an EV manufacturing plant in 2023 [124] and the operation of an onshore LIB recycling plant (TES-AMN group) has already commenced [125]. In contrast, a recent publication highlighting the efforts of Poland to develop onshore capability to recycle LIBs has shown that after 10 years of interest by a variety of stakeholders in the battery supply chain, it has not been able to develop, suggesting that government policies and monetary incentives play a key role [126]. Likewise, Australia's neighbours in the Asia-Pacific region are commencing their transition to renewable energy generation and storage and, therefore, opportunities exist for Australia to develop supply chains in the local region.…”
Section: Influence Of Global and Government Policies-lowering Emissio...mentioning
confidence: 99%
“…The obtained Li metals have a high purity (over 99%), and the produced Li 2 CO 3 is phase-pure without any remarkable secondary phase. Sobianowska-Turek et al [151] discussed the situation in the market of portable LIBs in the European Union (EU), focusing on Polish waste treatment management systems and disposal solutions. The work critically described current problems and deficiencies in the approaches to the end-of-life procedures for waste batteries and accumulators in the conditions of Poland and introduced possible future solutions.…”
Section: Others (Not Specified)mentioning
confidence: 99%
“…For the calculations, it was assumed that: 1) LIBs constitute 80% of batteries introduced to the market included in the group "other;" [7][8][9][10] 2) the annual growth of LIBs introduced into the market is equal to the average growth of these batteries in 2010-2018 and amounts to 5%; and 3) the collection rate of spent LIBs is equal to the annual minimum required level of collection of all types of portable waste batteries in a given year. [11] The performed forecast of the mass of collected waste LIBs by 2030 is shown in Figure 1.…”
Section: Introductionmentioning
confidence: 99%